Beta-1-Adrenergic Receptor Antibodies in Acute Coronary Syndrome: Is Less Sometimes More? - Ernst, Diana; Widera, Christian; Weiberg, Desiree; Derlin, Thorsten; Ahrenstorf, Gerrit; Sogkas, Georgios; Jablonka, Alexandra; Schmidt, Reinhold E.; Witte, Torsten; Heidecke, Harald; Riemekasten, Gabriela (Frontiers in Cardiovascular Medicine, 2018)
Background: Anti-beta-1-adrenergic receptor antibodies (anti-β1AR Ab) are associated with ischemic cardiomyopathies (ICM). Evidence continues to emerge supporting an autoimmune component to various cardiac diseases. This study compares anti-β1AR Ab concentrations in patients with different entities of acute coronary syndromes (ACS) to asymptomatic non-ACS patients with positron-emission computed tomography (PET/CT)-proven atherosclerosis, and healthy controls. Methods: Serum anti-β1AR Ab IgG concentrations were measured in 212 ACS patients, 100 atherosclerosis patients, and 62 controls using ELISA. All ACS patients underwent coronary angiography. All 374 patients participating completed a structured questionnaire regarding traditional cardiovascular risk factors. ACS patients were followed up for 6 months. Results: Patients with ACS exhibited lower anti-β1AR Ab levels compared to patients with atherosclerosis or healthy controls (both p<0.001). No differences in the ab levels were evident between healthy controls and patients with atherosclerosis. In the ACS groups, lower concentrations were found in patients with ST-elevation myocardial infarction (STEMI) (0.67 µg/ml) compared to patients with angina pectoris (AP) and non-ST elevation myocardial infarction (NSTEMI) (both 0.76 µg/ml, p=0.008). Anti-β1AR Ab levels ≤ 0.772 µg/ml were predictive for death and reinfarction (AUC 0.77, p = 0.006). No significant correlations between anti-β1AR Ab levels and atherosclerotic burden or traditional cardiovascular risk factors were identified. Conclusions: Lower anti-β1AR Ab concentrations appear to characterize ACS phenotypes and could serve as diagnostic and prognostic markers independent from traditional risk factors for atherosclerosis. The prognostic predictive value of anti-β1AR Ab in ACS remains to be confirmed in larger studies.